Chiral Calcium–BINOL Phosphate Catalyzed Diastereo‐ and Enantioselective Synthesis of syn‐1, 2‐Disubstituted 1, 2‐Diamines: Scope and Mechanistic Studies1. Issue 4 (21st November 2014) - Lalli, Claudia; Dumoulin, Audrey; Lebée, Clément; Drouet, Fleur; Guérineau, Vincent; Touboul, David; Gandon, Vincent; Zhu, Jieping; Masson, Géraldine
Abstract A highly enantioselective, chiral, Lewis acid calcium–bis(phosphate) complex, Ca[3 a]n, which catalyzes the electrophilic amination of enamides with azodicarboxylate derivatives 2 to provide versatile chiral 1, 2‐hydrazinoimines 4 is disclosed. The reaction gives an easy entry to optically active syn‐1, 2‐disubstituted 1, 2‐diamines 6 in high yields with excellent enantioselectivities, after a one‐pot reduction of the intermediate 1, 2‐hydrazinoimines 4. The geometry and nature of the N‐substituent of the enamide affect dramatically both the reactivity and the enantioselectivity. Although the calcium–bis(phosphate) complex was a uniquely effective catalyst, the exact nature of the active catalytic species remains unclear. NMR spectroscopy and MS analysis of the various calcium complexes Ca[3]n reveals that the catalysts exist in various oligomer forms. The present mechanistic study, which includes nonlinear effects and kinetic measurements, constitutes a first step in understanding these calcium–bis(phosphate) complex catalysts. DFT calculations were carried out to explore the mechanism and the origin of the enantioselectivity with the Ca[3]n catalysts.